The procurement, transmission, and abundance of bacteria in and among house flies (Musca domestica L.) - Thomson, Jessica Lynne (Kansas State University, 2019)
Microorganisms are a necessary component of house fly (Musca domestica L.) development. Animal manure and urban garbage are rich in microbes and may include human pathogens such as Salmonella enterica serovar Typhimurium. S. Typhimurium is a common food-borne pathogen shed by livestock which can potentially be vectored by adult house flies. Because the interaction of male and female house flies with cattle manure may differ due to differences in sex-specific nutritional requirements and behavior, the first objective of this dissertation was to determine if male and female house flies differ in bacteria acquired over time from cattle manure in the presence and absence of an alternative food source. Mated male and female adult house flies were exposed to cattle manure inoculated with either S. Typhimurium or non-pathogenic Escherichia coli in the presence (assay with both manure and sugar water provided) and absence (assay with manure only provided) of an alternative food source. Overall, female flies harbored more bacteria than males after exposure to S. Typhimurium or E. coli inoculated cattle manure; however, differences in abundance were only significant at 4 h and 12 h time points. Male and female house flies only differed in number of colony forming units (CFU) of E. coli at 4 h and 12 h time points in assays when both manure and sugar were provided likely due to sex-specific nutritional and behavioral differences; however, they differed in CFU of S. Typhimurium at 4 h and 12 h time points in both manure assays. Observations of the fly alimentary canal from manure-sugar assays supported these initial differences especially at 4 h where females held manure and fly food, while males held only sugar water. The initial differences in CFU S. Typhimurium at early time points regardless of the presence or absence of sugar may also have been attributed to differences in S. Typhimurium excretion rates. Because S. Typhimurium can survive and grow on fruits, such as cantaloupe, the second objective was to determine if house flies can transfer S. Typhimurium to and from cantaloupe and if cantaloupe facilitates the transfer of S. Typhimurium between flies. Adult female house flies (mated, 5-7 days old) were given ad libitum sugar water and were exposed to manure inoculated with sterile PBS (ST-) or S. Typhimurium (ST+) for 12 h. After manure exposure, to test for survival of S. Typhimurium, the ST+ flies were placed individually in empty jars and bacterial abundance was monitored over 24 h. To monitor the transmission of S. Typhimurium for 24 h after manure exposure, the flies were placed into jars containing either (1) a single ST+ fly with fresh cantaloupe (fly to food transmission), (2) four ST- flies with S. Typhimurium-inoculated cantaloupe (food to fly transmission), or (3) a single ST+ fly with four ST- flies with or without fresh cantaloupe (fly to fly transmission, with or without food). In all experiments, flies and cantaloupe (if present) were processed and cultured at 0, 6, 12, and 24 h after experimental setup for GFP S. Typhimurium abundance. S. Typhimurium survived in ST+ flies but decreased in total abundance over time even with cantaloupe present indicating that the flies were digesting the S. Typhimurium. The abundance of S. Typhimurium increased in both, inoculated cantaloupe and ST- flies, over time indicating that the S. Typhimurium was growing in the cantaloupe and flies were picking up S. Typhimurium from the cantaloupe. Additionally, in fly to fly transmission experiments, more ST- flies were positive for S. Typhimurium when cantaloupe was present. Therefore, presence of a shared food source likely facilitates fly-to-fly transfer. Because house flies have sex-specific behavioral and nutritional requirements and bacteria and coliform abundance differs across habitats, the final objective was to determine if house fly sex and habitat affect bacterial abundance and coliform abundance in house flies. Male and female house flies were collected from 3 different habitats (urban, sub-urban, agricultural) to determine if fly sex and location affected the total bacterial abundance and coliform abundance. Overall, house flies collected from the sub-urban site had the greatest mean CFU/fly of bacteria possibly due to males and females having equal access to microbe-rich substrates, while house flies collected from the urban site had the lowest mean CFU/fly of coliforms likely due to there being no immediate access to animal waste. Females were consistently greater in the mean CFU/fly of bacteria and coliforms than males within all sites, except for at the sub-urban site. Furthermore, females did not differ across sites in mean CFU/fly of bacteria and coliforms, most likely a result from females spending more time interacting with microbe-rich substrates, while males were highest at the sub-urban sites and lowest at the urban site suggesting that differences in male activity likely drive differences in bacterial and coliform abundance across habitats. Therefore, house fly sex and habitat affect the mean bacterial and coliform abundance in house flies. Results from all three objectives indicate that because house flies can acquire, harbor, and transmit S. Typhimurium to other flies in the presence of a food source, they have vector competence for S. Typhimurium. Furthermore, fly sex, habitat, and food source all should be considered in fly pest management programs to effectively reduce abundance of bacteria in and dissemination of pathogens by house flies, since house flies are key players in food safety and human and animal health.
Keywords: Musca domestica; House flies; Salmonella enterica; Bacterial acquisition; Pathogen transmission; Bacterial abundance